Titanium-based nanoscale ozone oxidation catalyst as well as preparation method and application thereof
Through the titanium-based nano-scale ozone oxidation catalyst, combined with the ρ-Al2O3 carrier and NiO@TiO2 active components, the treatment problem of difficult degradation of organic pollutants in industrial wastewater treatment is solved, and efficient, stable and environmentally friendly wastewater depth treatment effect is achieved.
Patent Information
- Application Number
- CN202411803990.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing industrial wastewater treatment technologies are difficult to effectively treat difficult-to-degrade organic pollutants. The traditional biological treatment effect is incomplete, and common catalysts have problems with metal active components loss and secondary pollution.
The stability and catalytic efficiency of the catalyst are improved by combining the ρ-Al2O3 support and NiO@TiO2 active components using a titanium-based nano-scale ozone oxidation catalyst. The method of preparing the catalyst includes pretreatment of the support, preparing the active ingredients, mixing and forming and drying steps.
It significantly improves the deep treatment effect of wastewater, reduces the treatment cost of the ozone method, and the stability and reuse ability of the catalyst are better than traditional catalysts, avoiding secondary pollution.
Smart Images

Figure BDA0005178725420000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a titanium-based nanoscale ozone oxidation catalyst, more specifically to an ozone oxidation catalyst for deep treatment of industrial wastewater, and further discloses a preparation method and application thereof. Background Art
[0002] Water is an important resource for human survival. According to the World Water Development Report 2021 released by UNESCO, global freshwater use has increased sixfold from 1921 to 2021. However, with the increase in sewage discharge, water quality faces severe challenges, especially the deterioration of the environment caused by industrialization, agricultural production and urban life. The current water resources situation is very worrying and has had an adverse impact on people's survival and social development. It is reported that global industrial activities discharge about 300-400 million tons of excessive heavy metals, difficult-to-decompose solvents, difficult-to-degrade organic matter, bacterial pathogens, etc. in waters every year, posing a huge threat to human life. At present, about 5 million people die from water quality-related diseases every year, and 200-300 million people suffer from related diseases. It can be seen that the discharge of industrial wastewater poses a serious threat to the natural environment and the living environment. The treatment of difficult-to-degrade industrial wastewater has always been a difficult problem and an urgent problem to be solved.
[0003] The traditional method for treating industrial wastewater is mainly biological method, which uses microorganisms or their secretions in nature to oxidize and decompose organic matter in wastewater, thereby purifying the wastewater. Although biological technology has the advantages of low cost, simple operation, and large processing capacity when treating sewage problems, for difficult-to-degrade industrial organic wastewater, traditional biological methods still have the problem of incomplete deep treatment and cannot achieve the expected purification effect. Therefore, this field urgently needs a wastewater deep treatment technology with strong pertinence, good treatment effect, and high efficiency.
[0004] At present, the main treatment technologies for industrial organic wastewater include membrane treatment technology, ozone catalytic oxidation technology, bio-enhancement technology, etc. Among them, ozone catalytic oxidation technology has attracted much attention due to its advantages such as strong oxidizing property and low pollution. According to the form of the catalyst, catalytic ozonation can be divided into homogeneous catalytic ozonation (the catalyst exists in the form of metal ions) and heterogeneous catalytic ozonation (the catalyst is a metal oxide solid or the metal / metal oxide is loaded on a solid phase carrier). Among them, the most effective way to treat industrial organic wastewater is heterogeneous catalytic ozone oxidation technology, which has the advantages of strong oxidizing property, simple operation, and small footprint. It can effectively realize the mineralization of difficult-to-degrade organic matter, and can also effectively solve the problems of homogeneous catalysts being difficult to recycle and secondary pollution. The main principle of heterogeneous catalytic ozone oxidation technology is: adsorbing ozone molecules through the active sites on the catalyst surface, decomposing them into more oxidizing active free radicals such as hydroxyl radicals and superoxide radicals, and reacting with organic pollutants in the water body, thereby realizing the mineralization of organic pollutants. Therefore, the key to the heterogeneous catalytic ozone oxidation process is an efficient catalyst, and researchers at home and abroad have conducted extensive research on this.
[0005] At present, there are many kinds of commonly used heterogeneous catalysts, mainly including single metal or multi-metal oxide catalysts containing Fe, Mn, Ce, Zn, Ti, etc., carbon-based non-metal catalysts containing elements such as N, F, and MOF catalysts. Among them, metal oxide catalysts are the most widely used due to their low cost and simple synthesis process. For example, Chinese patent CN102258997A discloses a manganese-loaded heterogeneous catalyst. Compared with the oxidation removal rate of pollutants by ozone alone, the water treatment method disclosed in the patent catalyzes ozone to produce highly active pentavalent manganese. The pollution removal efficiency can be increased by more than 70%. For another example, Chen et al. synthesized Fe-Cu@SiO2. The interfacial coupling between iron oxide and copper oxide and the strong interaction between SiO2 shell and metal improve the stability of the catalyst and have a good TOC removal rate. For another example, Moussavi et al. introduced the S element into MgO to prepare S-MgO catalyst, which can achieve 100% removal of tetracycline and 86.4% TOC removal rate within 60 minutes.
[0006] However, the main problem of conventional catalysts is the loss of active metal components of the catalyst, which can easily cause secondary pollution and increase the difficulty of subsequent treatment. In response to this problem, researchers have tried to enhance the stability of the catalyst from the perspective of strengthening the degree of bonding between the metal component and the carrier, and actively explored the influence of different synthesis methods on the stability of the catalyst. For example, Ahmadi et al. designed and synthesized the PAC@Fe3O4 catalyst by loading magnetic Fe3O4 on a carbon carrier (PAC), and explored its catalytic performance in ozone oxidation treatment of high-salt petrochemical wastewater (initial COD is about 362-400 mg / L). After 120 minutes of catalytic ozone oxidation by PAC@Fe3O4 catalyst, the removal rates of COD and TOC can reach 75.3% and 50.3%, respectively, with good ozone catalytic oxidation performance, but the COD and TOC removal efficiencies of the catalyst dropped to 58.3% and 41.1%, respectively, after repeated use, which is mainly attributed to the loss of Fe components in the surface active sites. During the 5 cycles of use, the Fe leaching concentration was between 0.05-0.2 mg / L. In addition, during the long-term ozone catalytic oxidation process, due to factors such as collision, the active components of the catalyst will be leached in trace amounts. If they accumulate in the water, they will still cause harm to the water environment. Therefore, there is an urgent need to find a green and efficient metal component to replace conventional transition metal oxides as the active center of ozone catalytic oxidation. Summary of the invention
[0007] To this end, the technical problem to be solved by the present invention is to provide a titanium-based nanoscale ozone oxidation catalyst, which has a simple preparation process, high catalytic efficiency, high stability, and can significantly reduce the processing cost of the ozone method;
[0008] The second technical problem to be solved by the present invention is to provide a preparation method and application of the above titanium-based nano-scale ozone oxidation catalyst.
[0009] In order to solve the above technical problems, the present invention discloses a titanium-based nanoscale ozone oxidation catalyst, which includes a ρ-Al2O3 carrier and a NiO@TiO2 active component.
[0010] Specifically, the titanium-based nanoscale ozone oxidation catalyst, the p-Al2O3 carrier is a spherical carrier;
[0011] Preferably, the diameter of the ρ-Al2O3 carrier is 3.0-5.0 mm.
[0012] The present invention also discloses a method for preparing the titanium-based nanoscale ozone oxidation catalyst, comprising the following steps:
[0013] (1) taking ρ-Al2O3 particles and pre-treating them to obtain the desired carrier for later use;
[0014] (2) Ni(NO3)2, urea and polyethylene glycol are mixed with water to obtain Ni(OH)2 through reaction; titanium-based compounds are added to perform precipitation reaction, and the solid is collected for amorphous TiO2 crystallization treatment to obtain the desired active component NiO@TiO2;
[0015] (3) mixing the ρ-Al2O3 carrier with the NiO@TiO2 active component and grinding the mixture;
[0016] (4) Continue to add seeds and the molding raw materials obtained in step (3) to carry out molding treatment, and the obtained catalyst body is dried.
[0017] Specifically, in the method for preparing the titanium-based nano-scale ozone oxidation catalyst, in the step (1), the pretreatment step includes the steps of cleaning and dust removal, surface oxidation removal, vacuum drying, and calcination to remove impurities from the ρ-Al2O3 particles;
[0018] Preferably, the cleaning and dust removal step includes the step of adding 60-70 v / v% ethanol solution for shaking cleaning;
[0019] Preferably, the surface deoxidation step includes the step of adding 40-50wt% nitric acid solution for treatment;
[0020] Preferably, the temperature of the vacuum drying step is 100-120°C, and the drying time is 6-10h;
[0021] Preferably, the temperature of the calcination and impurity removal step is 350-400° C., and the calcination time is 2-5 hours.
[0022] Specifically, in the method for preparing the titanium-based nanoscale ozone oxidation catalyst, in the step (2), the molar ratio of Ni(NO3)2, urea and polyethylene glycol is 1-2:5-10:1-2;
[0023] Preferably, the reaction temperature is 80-90°C.
[0024] Specifically, in the method for preparing the titanium-based nano-scale ozone oxidation catalyst, in the step (2), the titanium-based compound includes butyl titanate;
[0025] Preferably, the precipitation reaction comprises the steps of stirring at a temperature of 40-50° C. for 12-24 hours and precipitation for 1-3 hours.
[0026] Specifically, in the preparation method of the titanium-based nanoscale ozone oxidation catalyst, in the step (2), the amorphous TiO2 crystallization step includes a step of drying at 60-80°C for 2-4 hours and a step of calcining at 400-500°C for 1-2 hours.
[0027] Specifically, the method for preparing the titanium-based nanoscale ozone oxidation catalyst, in the step (2), further comprises the step of adding the prepared Ni(OH)2 into anhydrous ethanol for ultrasonic dispersion.
[0028] Preferably, the volume dosage of Ni(OH)2 is 2‰-15‰ of the volume of ethanol;
[0029] Preferably, the content of the active ingredient Ti of the titanium-based compound in ethanol is 0.01-0.95 mol / L.
[0030] Specifically, in the method for preparing the titanium-based nanoscale ozone oxidation catalyst, in the step (3), the grinding step includes the step of grinding using a nano-grinder.
[0031] Preferably, the grinding step is performed for 20-30 minutes.
[0032] Specifically, in the method for preparing the titanium-based nanoscale ozone oxidation catalyst, in the step (4), the seed comprises ρ-Al2O3;
[0033] Preferably, the speed of the molding process is 25-35r / min, and the molding time is 2-3h;
[0034] Preferably, the diameter of the catalyst embryo is 6-8 mm;
[0035] Preferably, the temperature of the drying step is 70-90° C., and the drying time is 6-10 days.
[0036] The invention also discloses the application of the titanium-based nano-scale ozone oxidation catalyst or the titanium-based nano-scale ozone oxidation catalyst prepared by the method in the field of ozone oxidation treatment of wastewater.
[0037] The titanium-based nano-scale ozone oxidation catalyst of the present invention comprises a ρ-Al2O3 carrier and a NiO@TiO2 active component. The catalyst of the present invention uses ρ-Al2O3 as a carrier and is prepared by a modified metal oxide to accelerate the decomposition of ozone. The ozone decomposition produces highly oxidizing hydroxyl radicals, which undergo substitution, addition, electron transfer, bond breaking and other reactions with organic matter. The hydroxyl radicals are non-selective when oxidizing organic pollutants and will not cause secondary pollution. The catalyst can oxidize and degrade large molecular refractory organic pollutants into low-toxic or non-toxic small molecular substances, thereby improving the biodegradability of wastewater.
[0038] The titanium-based nano-scale ozone oxidation catalyst of the present invention contains TiO2 in the active ingredient, which is a catalyst that is currently widely used and plays an important role in sewage treatment and environmental pollution control. Its good water solubility and catalytic performance are expected to solve the crisis in the sewage treatment and environmental treatment fields.
[0039] The titanium-based nano-scale ozone oxidation catalyst of the present invention, the multi-metal oxide with aluminum oxide as the carrier, has extremely high activity, not only has good wastewater treatment effect but also is convenient for recycling. Compared with the traditional single metal oxide catalyst, the catalyst of the present invention has a simple preparation process, high catalytic efficiency and high stability, and can significantly reduce the treatment cost of the ozone method.
[0040] The titanium-based nano-scale ozone oxidation catalyst of the present invention is placed in an ozone reactor, and can simultaneously carry out direct ozone oxidation and indirect oxidation of intermediate products. It is an advanced oxidation technology that integrates multiple functions. Compared with traditional ozone technology and Fenton technology, it has the advantages of high pollutant removal efficiency, high ozone utilization rate, and no need for external agents. Compared with traditional ozone oxidation catalysts, it has the characteristics of high catalytic activity, long catalyst life, and low operating cost.
[0041] The titanium-based nano-scale ozone oxidation catalyst of the present invention can promote the conversion of ozone into hydroxyl free radicals with stronger oxidation ability in the process of ozone oxidation treatment of wastewater, thereby improving the sewage treatment effect and rate. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] The preparation method of the titanium-based nanoscale ozone oxidation catalyst described in this embodiment comprises the following steps:
[0046] (1) Preparation of carrier: ρ-Al2O3 particles were added to a 65% by volume ethanol solution, and the solution was vibrated and cleaned at 30°C for three times to remove dust. The cleaned aluminum oxide was then added to a 45% by volume nitric acid solution to remove the oxide layer on the surface, and then washed with pure water. The solution was then dried at 100°C in a vacuum drying oven for 8 h, and then calcined at 350°C in a muffle furnace for 4 h to remove organic impurities in the pores and on the surface, thereby obtaining a pretreated carrier.
[0047] (2) Preparation of active components: Ni(NO3)2, urea, and polyethylene glycol were mixed in deionized water at a molar ratio of 1:5:1, and stirred continuously for 6 hours in a water bath at 80°C; after vacuum filtration, the mixture was washed with deionized water and ethanol to prepare Ni(OH)2; 0.15 g Ni(OH)2 was ultrasonically dispersed in 200 mL anhydrous ethanol for 20 minutes, and 2 mL of butyl titanate was dropped into the ethanol while magnetically stirring, and the mixture was stirred in a water bath at 45°C for 24 hours, precipitated for 2 hours, and the supernatant was removed. The obtained product was washed with ethanol and deionized water for 3 times; the product was dried at 80°C for 4 hours, and calcined at 450°C for 2 hours to crystallize the amorphous TiO2. The NiO@TiO2 active component of TiO2 coated NiO was prepared;
[0048] (3) Mixing: Weigh a certain amount of ρ-Al2O3 carrier and NiO@TiO2 active component, add them into a nano grinder for grinding, the grinding time is 30 min, ensure the mixing is uniform, and sieve them for later use;
[0049] (4) Molding and drying: Add ρ-Al2O3 as a seed into a molding machine, spray a small amount of deionized water and then soak at a certain speed of 30 r / min, add the molding raw materials mixed in step (3), repeat the feeding process until a catalyst embryo with a diameter of 6 mm is obtained, and the process time is 3.0 h; dry the catalyst embryo at 80°C for 8 days to fully dry the catalyst.
[0050] Example 2
[0051] The preparation method of the titanium-based nanoscale ozone oxidation catalyst described in this embodiment comprises the following steps:
[0052] (1) Preparation of carrier: ρ-Al2O3 particles were added to a 70% by volume ethanol solution, and the solution was vibrated and cleaned at 35°C for three consecutive times to remove dust; the washed aluminum oxide was then added to a 50% by volume nitric acid solution to remove the oxide layer on the surface, and the solution was cleaned with pure water, and then dried at 120°C in a vacuum drying oven for 6 hours, and then calcined at 400°C in a muffle furnace for 2 hours to remove organic impurities in the pores and on the surface, thereby obtaining a pretreated carrier;
[0053] (2) Preparation of active components: Ni(NO3)2, urea, and polyethylene glycol were mixed in deionized water at a molar ratio of 1.5:8:2, and stirred continuously for 5 h in a water bath at 90°C; after vacuum filtration, the mixture was washed with deionized water and ethanol to prepare Ni(OH)2; 0.2 g Ni(OH)2 was ultrasonically dispersed in 200 mL anhydrous ethanol for 20 min, and 5 mL butyl titanate was dropped into the ethanol while magnetically stirring, and the mixture was stirred in a water bath at 50°C for 24 h, precipitated for 3 h, and the supernatant was removed. The obtained product was washed with ethanol and deionized water for 3 times; dried at 80°C for 2 h, and the product was calcined at 500°C for 1 h to crystallize the amorphous TiO2. The NiO@TiO2 active component of TiO2-coated NiO was prepared.
[0054] (3) Mixing: Weigh a certain amount of ρ-Al2O3 carrier and NiO@TiO2 active component, add them into a nano grinder for grinding, the grinding time is 30 min, ensure the mixing is uniform, and sieve them for later use;
[0055] (4) Molding and drying: Add ρ-Al2O3 as a seed into the molding machine, spray a small amount of deionized water and then soak at a certain speed of 35 r / min, add the molding raw materials mixed in step (3), repeat the feeding process until a catalyst embryo with a diameter of 8 mm is obtained, and the process time is 3.0 h; dry the catalyst embryo at 90°C for 6 days to fully dry the catalyst.
[0056] Example 3
[0057] The preparation method of the titanium-based nanoscale ozone oxidation catalyst described in this embodiment comprises the following steps:
[0058] (1) Preparation of carrier: ρ-Al2O3 particles were added to a 60% by volume ethanol solution, and the solution was vibrated and cleaned at 25°C for three consecutive times to remove dust; the cleaned aluminum oxide was then added to a 40% by volume nitric acid solution to remove the oxide layer on the surface, and the solution was cleaned with pure water, and then dried at 100°C in a vacuum drying oven for 10 hours, and then calcined at 350°C in a muffle furnace for 5 hours to remove organic impurities in the pores and on the surface, thereby obtaining a pretreated carrier;
[0059] (2) Preparation of active components: Ni(NO3)2, urea, and polyethylene glycol were mixed in deionized water at a molar ratio of 2:10:1.5, and stirred continuously for 6 hours in a water bath at 80°C; after vacuum filtration, the mixture was washed with deionized water and ethanol to prepare Ni(OH)2; 0.2g Ni(OH)2 was ultrasonically dispersed in 200mL anhydrous ethanol for 20 minutes, and 3mL of butyl titanate was dropped into the ethanol while magnetically stirring, and the mixture was stirred for 12 hours in a water bath at 40°C, and precipitated for 2 hours. The supernatant was removed, and the obtained product was washed with ethanol and deionized water for 3 times; the mixture was dried at 60°C for 4 hours, and the product was calcined at 400°C for 2 hours to crystallize the amorphous TiO2. The NiO@TiO2 active component of TiO2 coated NiO was prepared;
[0060] (3) Mixing: Weigh a certain amount of ρ-Al2O3 carrier and NiO@TiO2 active component, add them into a nano-grinder for grinding for 20 min to ensure uniform mixing, and sieve them for later use;
[0061] (4) Molding and drying: Add ρ-Al2O3 as a seed into the molding machine, spray a small amount of deionized water and then soak at a certain speed of 25r / min, add the molding raw materials mixed in step (3), repeat the feeding process until a catalyst embryo with a diameter of 7mm is obtained, and the process time is 2.0h; the catalyst embryo is dried at 70°C for 10 days to fully dry the catalyst.
[0062] Example 4
[0063] The preparation method of the titanium-based nanoscale ozone oxidation catalyst described in this embodiment comprises the following steps:
[0064] (1) Preparation of carrier: ρ-Al2O3 particles were added to a 65% by volume ethanol solution, and the solution was vibrated and cleaned at 35°C for three consecutive times to remove dust; the washed aluminum oxide was then added to a 45% by volume nitric acid solution to remove the oxide layer on the surface, and the solution was cleaned with pure water, and then dried at 100°C in a vacuum drying oven for 8 hours, and then calcined at 350°C in a muffle furnace for 4 hours to remove organic impurities in the pores and on the surface, thereby obtaining a pretreated carrier;
[0065] (2) Preparation of active components: Ni(NO3)2, urea, and polyethylene glycol were mixed in deionized water at a molar ratio of 2:5:1, and stirred continuously for 6 hours in a water bath at 80°C; after vacuum filtration, the mixture was washed with deionized water and ethanol to prepare Ni(OH)2; 0.15 g Ni(OH)2 was ultrasonically dispersed in 200 mL anhydrous ethanol for 20 minutes, and 2 mL of butyl titanate was dropped into the ethanol while magnetically stirring, and the mixture was stirred in a water bath at 45°C for 24 hours, precipitated for 2 hours, and the supernatant was removed. The obtained product was washed with ethanol and deionized water for 3 times; the product was dried at 80°C for 4 hours, and calcined at 450°C for 2 hours to crystallize the amorphous TiO2. The NiO@TiO2 active component of TiO2 coated NiO was prepared;
[0066] (3) Mixing: Weigh a certain amount of ρ-Al2O3 carrier and NiO@TiO2 active component, add them into a nano grinder for grinding, the grinding time is 30 min, ensure the mixing is uniform, and sieve them for later use;
[0067] (4) Molding and drying: Add ρ-Al2O3 as a seed to the molding machine, spray a small amount of deionized water and then soak at a certain speed of 30r / min, add the molding raw materials mixed in step (3), repeat the feeding process until a catalyst embryo with a diameter of 6mm is obtained, and the process time is 3.0h; the catalyst embryo is dried at 80°C for 8 days to fully dry the catalyst.
[0068] Comparative Example 1
[0069] The preparation method of the ozone oxidation catalyst in this comparative example is the same as that in Example 1, the only difference being that the catalyst carrier is different, and the carrier is activated carbon.
[0070] Comparative Example 2
[0071] The preparation method of the ozone oxidation catalyst in this comparative example is the same as that in Example 1, the only difference being that a different nitrogen source is used in the preparation of the active component, and the nitrogen source is ammonium bicarbonate.
[0072] Comparative Example 3
[0073] The preparation method of the ozone oxidation catalyst in this comparative example is the same as that in Example 1, the only difference being that a different solvent is used in the preparation of the active component, and the solvent is propylene glycol.
[0074] Experimental example
[0075] 1. Catalytic effect
[0076] In 9 columnar reactors of the same specifications and an effective volume of 10 L, equal amounts of common alumina balls with the same particle size, commercially available carrier ozone catalysts (with alumina as the carrier and titanium dioxide as the catalytically active component) and nano-scale ozone oxidation catalysts prepared in Examples 1-4 of the present invention and Comparative Examples 1-3 were respectively filled, and coal gasification device wastewater (COD: 500 mg / L-1200 mg / L) was deeply treated under the same operating parameter conditions. The process conditions were: wastewater pH 7-8, ozone dosage 0.2 L / min, HRT 30 min, and catalyst dosage rate 80%.
[0077] The comparison of catalytic effects of different ozone oxidation catalysts is shown in Table 1.
[0078] Table 1 Catalytic effect
[0079] Filling Type <![CDATA[Influent COD / (mg·L -1 )]]> <![CDATA[Effluent COD / (mg·L -1 )]]> COD removal rate / % Ordinary alumina balls 679 477 29.8 Commercially available ozone catalysts 558 302 45.9 Example 1 931 315 66.1 Example 2 780 309 60.4 Example 3 590 238 59.7 Example 4 931 354 62.0 Comparative Example 1 1038 502 51.6 Comparative Example 2 665 350 47.4 Comparative Example 3 1296 519 59.9
[0080] It can be seen that under the same operating conditions, the catalytic effect of the catalyst prepared by the present invention is much higher than that of ordinary alumina balls. Compared with the commercially available ozone catalyst with titanium dioxide as the active component, the COD removal rate is increased by nearly 20%, indicating that the catalytic performance of the ozone oxidation catalyst prepared by the present invention is excellent. The Ni and Ti ions in the catalyst were dissolved to 0.0021 mg / L and 0.00075 mg / L respectively after 20 days, and the dissolution concentrations of the ions were far lower than the concentrations specified by the existing national drinking water standards, indicating that the ozone oxidation catalyst prepared by the present invention has good reusability and will not cause secondary pollution.
[0081] 2. Wastewater treatment effect
[0082] Eight columnar reactors of the same specifications and an effective volume of 10 L were filled with equal amounts of nano-scale ozone oxidation catalysts prepared in Example 1 of the present invention and Comparative Example 3 of the same particle size, and several different wastewaters were deeply treated under the same operating parameter conditions. The process conditions were: ozone dosage of 0.2 L / min, HRT of 30 min, and catalyst dosage rate of 80%.
[0083] The effluent treatment effects of wastewater biochemical pools in different industries are shown in Table 2.
[0084] Table 2 Wastewater treatment effect
[0085]
[0086] It can be seen from the data in Table 2 that under certain operating conditions, the COD removal rate of the ozone oxidation catalyst prepared by the present invention for different types of wastewater is 50-65%, which is 20-35% compared with the direct ozone oxidation COD removal rate, and the removal rate is increased by nearly 30%; compared with the COD removal rate of the ozone oxidation catalyst prepared in Comparative Example 3, which is 30-46%, the removal rate is increased by 10%-20%, and the ozone oxidation catalyst prepared by the present invention has a broad spectrum of catalytic performance for antibiotic ozone oxidation degradation. After 18 days of continuous use, the removal rate of the catalyst for COD in wastewater did not decrease significantly, and stabilized at 50.2%-62.8%, indicating that the catalyst has good application stability.
[0087] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A titanium-based nanoscale ozone oxidation catalyst, characterized in that: The catalyst includes a ρ-Al2O3 carrier and a NiO@TiO2 active component.
2. The titanium-based nanoscale ozone oxidation catalyst according to claim 1, characterized in that: The p-Al2O3 carrier is a spherical carrier; Preferably, the diameter of the ρ-Al2O3 carrier is 3.0-5.0 mm.
3. A method for preparing the titanium-based nanoscale ozone oxidation catalyst as claimed in claim 1 or 2, characterized in that: The steps include: (1) taking ρ-Al2O3 particles and pre-treating them to obtain the desired carrier for later use; (2) Ni(NO3)2, urea and polyethylene glycol are mixed with water to obtain Ni(OH)2 through reaction; titanium-based compounds are added to perform precipitation reaction, and the solid is collected for amorphous TiO2 crystallization treatment to obtain the desired active component NiO@TiO2; (3) mixing the ρ-Al2O3 carrier with the NiO@TiO2 active component and grinding the mixture; (4) Continue to add seeds and the molding raw materials obtained in step (3) to carry out molding treatment, and the obtained catalyst body is dried.
4. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to claim 3, characterized in that: In the step (1), the pretreatment step includes the steps of cleaning and dust removal, surface oxidation removal, vacuum drying, and calcination to remove impurities from the ρ-Al2O3 particles; Preferably, the cleaning and dust removal step includes the step of adding 60-70 v / v% ethanol solution for shaking cleaning; Preferably, the surface deoxidation step includes the step of adding 40-50wt% nitric acid solution for treatment; Preferably, the temperature of the vacuum drying step is 100-120°C, and the drying time is 6-10h; Preferably, the temperature of the calcination and impurity removal step is 350-400° C., and the calcination time is 2-5 hours.
5. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to claim 3 or 4, characterized in that: In the step (2), the molar ratio of Ni(NO3)2, urea and polyethylene glycol is 1-2:5-10:1-2; Preferably, the reaction temperature is 80-90°C.
6. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to any one of claims 3 to 5, characterized in that: In the step (2), the titanium-based compound includes butyl titanate; Preferably, the precipitation reaction comprises the steps of stirring at a temperature of 40-50° C. for 12-24 hours and precipitation for 1-3 hours.
7. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to any one of claims 3 to 6, characterized in that: In the step (2), the amorphous TiO2 crystallization step includes a step of drying at 60-80°C for 2-4 hours and a step of calcining at 400-500°C for 1-2 hours.
8. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to any one of claims 3 to 7, characterized in that: In the step (3), the grinding step includes the step of grinding using a nano-grinder; Preferably, the grinding step is performed for 20-30 minutes.
9. The method for preparing the titanium-based nanoscale ozone oxidation catalyst according to any one of claims 3 to 8, characterized in that: In the step (4), the seed comprises ρ-Al2O3; The speed of the molding process is 25-35r / min, and the molding time is 2-3h; Preferably, the diameter of the catalyst embryo is 6-8 mm; Preferably, the temperature of the drying step is 70-90° C., and the drying time is 6-10 days.
10. Use of the titanium-based nano-scale ozone oxidation catalyst according to claim 1 or 2 or the titanium-based nano-scale ozone oxidation catalyst prepared by the method according to any one of claims 3 to 9 in the field of ozone oxidation treatment of wastewater.
Citation Information
Patent Citations
A manganese-supported heterogeneous catalyst and a water treatment method utilizing it to catalyze ozone to generate highly active pentavalent manganese.
CN102258997A
Ozone catalytic oxidation catalyst for treating reverse osmosis concentrated water and preparation method of catalyst
CN105618080A
Loaded ozonation catalyst and preparation method and application thereof
CN106345450A
Organic waste water ozone oxidation catalyst and preparation method and application thereof
CN110152682A
Ozone catalyst, preparation method thereof and method for treating industrial wastewater
CN110314678A